Children with a star : Jewish youth in Nazi Europe - Dwork, Deborah (Yale University Press, 1991)
Based on many oral histories taken from child survivors of the Holocaust, the author focuses on the experiences of young Jewish children from their earliest encounters with anti-Semitism to their enslavement in labor camps.